Institutional tuberculosis infection control in a rural sub-district in South Africa: A quality improvement study - Martha B. Mekebeb; Klaus von Pressentin; Louis S. Jenkins (AOSIS, 2019)
Background: Tuberculosis (TB) is a major global health challenge, and South Africa is one of the high-burden countries. A national TB infection control (TBIC) guideline has stipulated three areas of infection control at health facilities: work practice and administrative control, environmental control, and personal protection for health workers. Aim: The aim of this study was to identify the gaps and address the challenges in institutional TBIC. Setting: The district hospital and a primary health care clinic within the Mossel Bay sub-district in the Western Cape. Methods: According to the national TBIC draft guideline, a quality improvement cycle was used to evaluate and improve TBIC. Each facility had an existing infection and prevention control and occupational health and safety team, which were used as the audit teams. Results: A baseline assessment was followed by a set of interventions, which did not show a significant improvement in TBIC. The difference between the pre- and post-intervention TB screening rate was not statistically significant. An assessment of time interval between 101 patients presenting with TB symptoms and diagnosed with TB was 4 days at baseline and post-intervention. Most of the anticipated improvements were dependent on the health workers' adherence to the local TBIC policies, which emerged as an unexpected finding. Conclusion: We found good managerial commitment reflected by the presence of various policies, guidelines, specific personnel and committees to deal with infection control in general. This study has created awareness about TBIC among staff and pointed out the complexity of health workers' behaviour towards adhering to policies.